2013
DOI: 10.1097/bpo.0b013e3182745439
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between the Child Health Questionnaire and the International Knee Documentation Committee Score in Pediatric and Adolescent Patients With an Anterior Cruciate Ligament Tear

Abstract: Level III cross-sectional study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 29 publications
1
30
1
Order By: Relevance
“…The COSMIN statement does not include a statement specifying the cut-off value necessary for a strong correlation. Thus, we used a cut-off of 0.5 to remain consistent with previous studies and recommendations 9 19 21 24 25. We recognise that there is currently a debate regarding the appropriate cut-off value for a strong correlation, with values ranging from 0.5 to 0.7 9 19 21 24–27.…”
Section: Discussionmentioning
confidence: 90%
“…The COSMIN statement does not include a statement specifying the cut-off value necessary for a strong correlation. Thus, we used a cut-off of 0.5 to remain consistent with previous studies and recommendations 9 19 21 24 25. We recognise that there is currently a debate regarding the appropriate cut-off value for a strong correlation, with values ranging from 0.5 to 0.7 9 19 21 24–27.…”
Section: Discussionmentioning
confidence: 90%
“…Boykin et al 6 demonstrated a strong correlation between knee function and psychological health among pediatric patients with ACL tears. Importantly, young athletes with a strong athletic identity were shown to correlate their self-worth and image with their sports involvement.…”
mentioning
confidence: 99%
“… 23 Quality of life measures have also been significantly linked to ACL surgery outcomes with regards to physical, emotional and social functioning. 24 In addition, subtle changes in knee mechanics may lead patients to have trouble getting back to a pre-injury state and this may lead to psycho-social complications.…”
Section: Discussionmentioning
confidence: 99%